Costner Oauth2 user creation - Hinrik Már Hreinsson 1989- (2017)
In this report the second half of 6 etc B.Sc project Costner Oauth2 user creation is discussed. This project was conducted at Reykjavík University in fall of 2016 in collaboration with Costner ehf. In the project a user creation process for Costner Captain education overview platform was developed using Oauth2 authorization framework and flask. The user creation will eventually be used by school administration to create new user for the Costner system. Texting inniheldur upplýsingar um innskráningu notenda hjá Costner kerfinu og því er óskast eftir því að hún sé lokuð. Því það eru ekki upplýsingar sem ættu að vera öllum aðgengilegar